Empowering Communities in the Development of Regenerative Tourism in Koja Doi Tourism Village, Sikka Regency, East Nusa Tenggara Province - Michael Rudolfus Sawu; I Made Adikampana; I Nyoman Sukma Arida (Asian Journal of Social and Humanities, 2024)
This research aims to analyze the existing conditions of regenerative tourism development, the level of local community participation and propose an empowerment model in the development of regenerative tourism. Qualitative research with a verification approach is used to analyze research problems. Data is collected through observation, interviews, documentation and literature studies related to the subject being researched. The data analysis technique used is qualitative thematic. The informants involved in this research were local communities, regional government, non-governmental organizations, academics and tourists. The findings of this research are the existence of regenerative tourism practices by local communities and tourists. Local communities have positive attitudes and also tourists' perceptions of regenerative tourism practices. However, tourists want improvements in several other aspects. The level of local community participation in regenerative tourism entrepreneurship was found to be still minimal. This is due to human resources, economic capital and partnerships to manage a regenerative tourism business. The implication of this research is to create opportunities to optimize empowerment efforts to suit the needs and potential of local communities.